Pengaruh Promosi Terhadap Perolehan Laba pada UKM Keripik Cinta Kecamatan Gebang Langkat - Rinda Rindiani; Azhar; Anjur Perkasa Alam (Institut Syekh Abdul Halim Hasan Binjai, 2022)
The business world is a business world full of risk and uncertainty, that is, between success and failure, it happens easily and quickly. Entrepreneurship can be interpreted as a process, namely the process of creating new (new creations) and making something different from existing ones (innovation). While entrepreneurship refers to people who carry out the process of creating wealth/wealth and added value, through reasoning and generating ideas, combining resources and realizing these ideas into reality. The research approach used in this study is associative (relationship), associative research is research that aims to determine the relationship between two or more variables. The results of the study, there is a significant influence between promotions on profits for UKM Keripik Cinta Mas Hendro Kec. Gbang Langkat. This is evidenced by the results of the hypothesis test, namely the t-test with a significance value greater than 0.05 (0.30 > 0.05) and a tcount < t table (2.268 > 2.02809), so there is no effect of variable X on variable Y. The promotions carried out affect the profit of the Keripik Cinta Mas Hendro Kec. Gebang Langkat is only 10.9%, while the remaining 89.1% (100% - 10.9%) is influenced by other variables such as the pandemic, sales, location, salary expenses, expenses, and others. There is a positive relationship between Promotions (X) and Profits (Y), the more frequent and effective the promotions carried out by UKM Keripik Cinta Mas Hendro Kec. Gebang Langkat then the acquisition of profit at UKM Cinta Chips Mas Hendro Kec. Gebang Langkat will increase even though it is not significant.